Ibrutinib-Associated Cardiotoxicity: From the Pharmaceutical to the Clinical - Dong R; Yan Y; Zeng X; Lin N; Tan B (Dove Medical Press, 2022)
Rong Dong,1 Youyou Yan,2 Xiaokang Zeng,3 Nengming Lin,1,2 Biqin Tan1 1Department of Clinical Pharmacy, Key Laboratory of Clinical Cancer Pharmacology and Toxicology Research of Zhejiang Province, Affiliated Hangzhou First People's Hospital, Zhejiang University School of Medicine, Hangzhou, 310006, People's Republic of China; 2Translational Medicine Research Center, Affiliated Hangzhou First People's Hospital, Zhejiang University School of Medicine, Hangzhou, Zhejiang, 31006, People's Republic of China; 3Department of Critical Care Medicine, Affiliated Hangzhou First People's Hospital, Zhejiang University School of Medicine, Hangzhou, Zhejiang, 31006, People's Republic of ChinaCorrespondence: Biqin Tan, Department of Clinical Pharmacy, Affiliated Hangzhou First People's Hospital, Zhejiang University School of Medicine, Room 207, No. 5 Building, Hangzhou, People's Republic of China, Tel +86-571-56007824, Fax +86-571-56005600, Email biqintan@zju.edu.cn Nengming Lin, Department of Clinical Pharmacy, Affiliated Hangzhou First People's Hospital, Zhejiang University School of Medicine, Room 903, No. 7 Building, Hangzhou, People's Republic of China, Tel/Fax +86-571-56005600, Email lnm1013@zju.edu.cnAbstract: Ibrutinib is the first-in-class Bruton tyrosine kinase (BTK) inhibitor that has revolutionized the treatment of B cell malignancies. Unfortunately, increased incidences of cardiotoxicity have limited its use. Despite over a decade of research, the biological mechanisms underlying ibrutinib cardiotoxicity remain unclear. In this review, we discuss the pharmacological properties of ibrutinib, the incidence and mechanisms of ibrutinib-induced cardiotoxicity, and practical management to prevent and treat this condition. We also synopsize and discuss the cardiovascular adverse effects related to other more selective BTK inhibitors, which may guide the selection of appropriate BTK inhibitors.Keywords: ibrutinib, cardiotoxicity, BTK inhibitors, atrial fibrillation, cardio-oncology